Pharmaceutical Values of Calycosin: One Type of Flavonoid Isolated from Astragalus. (7th May 2021) - Gong, Guowei; Zheng, Yuzhong; Yang, Yang; Sui, Yixuan; Wen, Zhen
Abstract : Astragalus is a popular Materia Medica in China, and it could be applied in the treatment of various diseases. It contains a variety of chemically active ingredients, such as saponins, flavonoids, and polysaccharides. Plant-derived bioactive chemicals are considered natural, safe, and beneficial. Among the infinite plant-identified and isolated molecules, flavonoids have been reported to have positive effects on human health. Calycosin is the most important active flavonoid substance identified predominantly within this medicinal plant. In recent years, calycosin has been reported to have anticancer, antioxidative, immune-modulatory, and estrogenic-like properties. This review collected recent relevant literatures on calycosin and summarized its potential pharmaceutical properties and working mechanism involved, which provided solid basis for future clinical research.